2016
DOI: 10.1016/j.neuro.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects of methamphetamine and alpha-PVP vapor and injection

Abstract: Vaporizing drugs in e-cigarettes is becoming a common method of administration for synthetic cathinones and classical stimulants. Heating during vaporization can expose the user to a cocktail of parent compound and thermolytic degradants, which could lead to different toxicological and pharmacological effects compared to ingesting the parent compound alone via injection or nasal inhalation. This study examined the in vivo toxicological and pharmacological effects of vaporized and injected methamphetamine (METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 43 publications
4
23
0
1
Order By: Relevance
“…In contrast, α-PVP contains a pyrrolidine ring, which produces DA and NE transporter blockade (Glennon and Young 2016;Marusich et al 2014). Despite a different mechanism of action, α-PVP and 4MMC produce typical stimulant effects including hyperactivity and stereotyped behavior (Marusich et al 2014;Marusich et al 2012;Marusich et al 2016). Importantly, α-PVP and 4MMC are readily self-administered by rats, indicating a propensity for addiction (Aarde et al 2015;Creehan et al 2015;Nguyen et al 2017a;Nguyen et al 2017b;Vandewater et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, α-PVP contains a pyrrolidine ring, which produces DA and NE transporter blockade (Glennon and Young 2016;Marusich et al 2014). Despite a different mechanism of action, α-PVP and 4MMC produce typical stimulant effects including hyperactivity and stereotyped behavior (Marusich et al 2014;Marusich et al 2012;Marusich et al 2016). Importantly, α-PVP and 4MMC are readily self-administered by rats, indicating a propensity for addiction (Aarde et al 2015;Creehan et al 2015;Nguyen et al 2017a;Nguyen et al 2017b;Vandewater et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Results reported here serve as proof-of-principle for a novel device capable of translationally relevant delivery of nicotine aerosol for use in mechanistic studies of behavioral and biological effects of e-cigarettes. This apparatus has also been used to deliver aerosolized stimulants to rodents (Marusich et al, 2016). …”
Section: 0 Introductionmentioning
confidence: 99%
“…For example, Aarde and colleagues (2015) reported that in rats α-PVP was similar to MDPV in both potency and efficacy in supporting intravenous self-administration (see also Schindler et al, 2015). Additionally, Watterson et al (2014) demonstrated that in rats α-PVP dose-dependently decreased ICSS thresholds in a discrete trials current threshold procedure (Marusich et al, 2016). Consistent with this, Gatch et al (2015) reported that in mice α-PVP induced significant dose-dependent conditioned place preferences.…”
Section: Introductionmentioning
confidence: 99%